2020
DOI: 10.4271/2020-01-1625
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Corrosion Proof Braking System

Abstract: <div class="section abstract"><div class="htmlview paragraph">The manuscript firstly overviews the corrosion potentials of several components used in disk-brake systems. Particular attention is devoted to the couplings between materials with different nobility. It is demonstrated that if two materials: a) show a difference in their corrosions potential (E<sub>corr</sub>) &gt;100mV; and b) are in electric contact in the presence of an electrolyte; they can form a galvanic couple (GC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…This value seems particularly high, indeed in the case of pure Al the potential fall in the range −720 ÷ −880 mV vs. SCE. 32 In addition, it is possible to detect the presence of horizontal lines (see top left corner of Fig. 6B) which can be associated with the polishing of the material prior to SKP measurement and related modification of the electrode surface.…”
Section: Resultsmentioning
confidence: 99%
“…This value seems particularly high, indeed in the case of pure Al the potential fall in the range −720 ÷ −880 mV vs. SCE. 32 In addition, it is possible to detect the presence of horizontal lines (see top left corner of Fig. 6B) which can be associated with the polishing of the material prior to SKP measurement and related modification of the electrode surface.…”
Section: Resultsmentioning
confidence: 99%
“…An important characteristic of brake discs is their resistance level against corrosion, which is also observed in the publications [55][56][57]. Corrosion on the friction surfaces of brake discs can cause an excessive increase in the temperature of brake discs and brake pads, as well as a reduction in the coefficient of friction, resulting in the reduction in braking force and lengthening of stopping distance [58].…”
Section: Introductionmentioning
confidence: 83%
“…The manuscript [55] aimed at demonstrating that the fine-tuning of alloying elements in cast iron is a particularly effective method in order to improve its corrosion resistance, thus allowing the development of future disc brake rotors with a prolonged operating life. The authors in the publication [57] concluded that it is possible to mitigate the corrosion of cast iron brake discs by modulating the carbon morphology, alloy element concentration and microstructure. Increasing the corrosion resistance is also possible via ferritic nitrocarburizing (FNC), as also mentioned in the publication [73], in which the authors studied the effect of the brake friction value by FNC compound layer thickness with scaled dynamometer testing, and determined the anti-corrosion performance results for each respective case via complex environment salt spray testing.…”
Section: Introductionmentioning
confidence: 99%